2022
DOI: 10.3390/vaccines10081192
|View full text |Cite
|
Sign up to set email alerts
|

Design of Multi-Epitope Vaccine for Staphylococcus saprophyticus: Pan-Genome and Reverse Vaccinology Approach

Abstract: Staphylococcus saprophyticus is a Gram-positive coccus responsible for the occurrence of cystitis in sexually active, young females. While effective antibiotics against this organism exist, resistant strains are on the rise. Therefore, prevention via vaccines appears to be a viable solution to address this problem. In comparison to traditional techniques of vaccine design, computationally aided vaccine development demonstrates marked specificity, efficiency, stability, and safety. In the present study, a novel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…In recent years, several in silico screening pipelines have emerged to predict the binding affinity between the pHLA pair, which greatly facilitates the design of peptide vaccines. Notable tools, including NetMHCPan and NetMHCIIPan, [ 55 ] have been employed in the peptide selection processes for developing vaccines against pathogens such as Staphylococcus saprophyticus [ 19 ], MERS-CoV [ 14 ] and SARS-CoV-2 [ 13 , 16 , 17 ]. Additionally, HLAPred was utilized in the design of a peptide vaccine against Dermatophagoides pteronyssinus [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, several in silico screening pipelines have emerged to predict the binding affinity between the pHLA pair, which greatly facilitates the design of peptide vaccines. Notable tools, including NetMHCPan and NetMHCIIPan, [ 55 ] have been employed in the peptide selection processes for developing vaccines against pathogens such as Staphylococcus saprophyticus [ 19 ], MERS-CoV [ 14 ] and SARS-CoV-2 [ 13 , 16 , 17 ]. Additionally, HLAPred was utilized in the design of a peptide vaccine against Dermatophagoides pteronyssinus [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that the designed vaccine construct can produce cytokines in high titers, and thus, indicating our vaccine to be a good candidate for vaccine development against the Zika virus ( 43 , 47 ). The predicted cytokines also help in mediating cellular base immune in order to eradicate the pathogens ( 48 , 49 ). Receptor molecular docking studies were conducted to analyze the binding interface between designed immune cells and vaccination, as this interaction is crucial for producing an immune response against specific pathogens ( 21 , 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…In comparison to conventional vaccines or single-epitope vaccines, multi-epitope vaccine constructs (MEPVC) are robust (32,33). They are thought to simultaneously elicit strong and broad-spectrum humoral and cellular immune responses (34). These vaccines are frequently conjugated with adjuvants, which is thought to create prolonged immune responses and boost immunogenicity while minimizing the presence of any Diagram showing the framework that was created to highlight prospective monkeypox vaccine candidate, followed by the anticipation of antigenic B cell derived T cell epitopes.…”
Section: Chimeric Mempv Constructionmentioning
confidence: 99%